Continuous wave laser induced third‐order nonlinear optical properties of conducting polymers. Issue 10 (2nd June 2015) - Pramodini, S.; Poornesh, P.
<x xml:space="preserve">Abstract</x> We report the studies on the third‐order optical nonlinearity and optical power limiting properties of conducting polymers viz., poly(o‐anisidine) and polypyrrole. Continuous wave (CW) He–Ne laser operating at 633 nm was used as the source of excitation. Ultraviolet‐Visible (UV–VIS) spectroscopy measurement reveals that the absorption bands are continuous and wide and hence can be used for photovoltaic applications. Fourier transform infrared spectroscopy (FTIR) was performed to elucidate the structure of polymers. Z‐scan technique was employed to determine the real and imaginary parts of third‐order nonlinear susceptibility χ(3), nonlinear absorption coefficient βeff, and nonlinear index of refraction n2. The estimated values of βeff, n2, and χ(3) are of the order of 10−2 cm/W, 10−5 esu, and 10−7 esu, respectively. The presence of large number of electron donating groups in the structure, leads to efficient charge transfer and results in the increase in conjugation length. The increase in conjugation length in turn increases the χ(3) value. Induced self‐diffraction rings were observed when the samples were exposed to laser beam due to thermal lensing and refractive index change. Good optical limiting and clamping behavior was achieved for various sample concentrations. These studies indicate that the polymers are a suitable candidate for photonic applications. POLYM. ENG. SCI., 55:2396–2402, 2015. © 2015 Society of Plastics Engineers